A comparative analysis of process safety management (PSM) systems in the process industry. (July 2020) - Nwankwo, Chizaram D.; Theophilus, Stephen C.; Arewa, Andrew O.
Abstract: The root cause of most accidents in the process industry has been attributed to process safety issues ranging from poor safety culture, lack of communication, asset integrity issues, lack of management leadership and human factors. These accidents could have been prevented with adequate implementation of a robust process safety management (PSM) system. Therefore, the aim of this research is to develop a comparative framework which could aid in selecting an appropriate and suitable PSM system for specific industry sectors within the process industry. A total of 21 PSM systems are selected for this study and their theoretical frameworks, industry of application and deficiencies are explored. Next, a comparative framework is developed using eleven key factors that are applicable to the process industry such as framework and room for continuous improvement, design specification, industry adaptability and applicability, human factors, scope of application, usability in complex systems, safety culture, primary or secondary mode of application, regulatory enforcement, competency level, as well as inductive or deductive approach. After conducting the comparative analysis using these factors, the Integrated Process Safety Management System (IPSMS) model seems to be the most robust PSM system as it addressed almost every key area regarding process safety. However, inferences drawn from study findings suggest that there is still no one-size-fits-all PSM system for all sectors of the process industry. Highlights: PSM systems can be implemented based on their levels of flexibility and robustness. The Integrated PSM system (IPSMS) model seems to be the most robust and flexible PSM system. There is no absolute best-fit PSM system for all sectors of the process industry. Selecting the right PSM system can be pivotal for reducing process accidents.